2016
DOI: 10.1080/08916934.2016.1191476
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the multidrug resistance-1 gene on drug resistance in primary immune thrombocytopenia

Abstract: Primary immune thrombocytopenia (ITP) is an autoimmune disorder that is characterized by low platelet count. Glucocorticoids (GCs) resistance is a great challenge in the treatment of ITP. P-glycoprotein (P-gp) is a widely studied protein, which is associated with drug resistance. However, in ITP, the functional activity and immune regulation mechanism of P-gp remain uncertain. In this study, we evaluated the expression and functional activity of P-gp in different lymphocyte subsets, explored the correlation be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 46 publications
0
3
0
Order By: Relevance
“…A limitation of our study is the lack of PBMCs to confirm the synergistical effect of CEP and MP and their action mechanism. It is possible to further investigate the role of CEP on MP pharmacodynamics and their action mechanism by using PBMCs with over-functional P-glycoprotein isolated from non-responsive ITP patients [ 12 ]. Although, Cepharanthin ® combined with GC were confirmed to be useful in the management of chronic ITP [ 1 , 8 ], we look forward to new clinical reports which compare the effects of CEP and Cepharanthin ® combined with GC for non-responsive ITP patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A limitation of our study is the lack of PBMCs to confirm the synergistical effect of CEP and MP and their action mechanism. It is possible to further investigate the role of CEP on MP pharmacodynamics and their action mechanism by using PBMCs with over-functional P-glycoprotein isolated from non-responsive ITP patients [ 12 ]. Although, Cepharanthin ® combined with GC were confirmed to be useful in the management of chronic ITP [ 1 , 8 ], we look forward to new clinical reports which compare the effects of CEP and Cepharanthin ® combined with GC for non-responsive ITP patients.…”
Section: Discussionmentioning
confidence: 99%
“…It transports a variety of substrates, including GC, out of the immune cells [ 11 ]. Over-functional P-glycoprotein has been reported to play an important role in the pathogenesis of ITP and to reduce the immunosuppressive efficacy of GCs in non-responsive ITP patients [ 12 ]. Our previous study suggested that CEP strongly inhibited P-glycoprotein function in T lymphocytic leukemia daunorubicin resistant MOLT-4 cells (MOLT-4/DNR), whereas isotetrandrine and berbamine, the other two components of Cepharanthin ® , showed extremely weak inhibitory effects on P-glycoprotein function [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, P-gp regulation is complex. Factors, such as drugs, cytokines, gene polymorphisms, and oncogenes, can affect the expression of P-gp [ 6 ]. In addition to serving as the primary treatment for RA, MTX is a specific substrate of P-gp [ 7 ].…”
Section: Introductionmentioning
confidence: 99%